Analysis Of Understanding Of Chemical Concepts Reviewed From Intellectual Intelligence (Iq) And Adverse Resistance Intelligence (Aq) - Nursa’adah, Fatwa Patimah; Rosa, Novrita Mulya (PT. Hafasy Dwi Nawasena, 2024)
Universities play an important role in the development of individuals who are skilled and ready to face challenges in the professional world. It is important to investigate the various factors that influence students' success in their educational endeavors to ensure they can reach their maximum potential. This study aims to examine the effect of intellectual intelligence (IQ) and resilience (AQ) on chemistry concept understanding (PK) among students in the Mathematics Education program. In this study, participants were randomly selected to ensure accuracy and fair representation of the student population. The data collected were analyzed using multiple regression techniques, which allow researchers to look at the relationship between multiple independent variables and the dependent variable simultaneously. The results of this study show that IQ and AQ together have a significant impact on the understanding of chemical concepts. In addition, individually, both IQ and AQ also show a significant influence on the understanding of chemical concepts. In other words, students with higher levels of intellectual intelligence and better resilience abilities tend to have a deeper understanding of chemistry concepts. These findings emphasize the importance of developing not only cognitive aspects but also non-cognitive aspects such as resilience in the educational process. This can help in designing educational programs that are more comprehensive and effective in preparing students for future academic and professional challenges.